The Issue of Racial Profiling in Traffic Stop Citations - Vito, Anthony Gennaro (Journal of contemporary criminal justice, 2017)
This study addresses racial profiling when the traffic stop outcome is a citation. This study uses focal concerns theory as a theoretical explanation for police officer decision-making while using propensity score matching to provide similarly situated drivers based on race and/or gender. This study uses traffic stop data (N = 48,586) collected by the Louisville Police Department between January 1 and December 31, 2002. The statistical results show that focal concerns theory components matter the most for traffic stop data even though racial profiling is still an issue. Propensity score matching is a statistical technique that provides a better way to determine whether racial profiling was evident. Gender was not significant for female drivers. This study advances our understanding of race and traffic stop citations using a theoretical explanation.